On Ethics: A Propos of Antigone - Philippe Lacoue-Labarthe (EJP import test, 2018)
Lecture held in may 1990, published, in French, in Collège International de Philosophie, ed., Lacan et les philosophes (Paris: Albin Michel, 1991), pp. 21-36. Allow me to inscribe here the following excerpt from Jacques Lacan’s text: "The register of being of he who could be placed by a name must by necessity be preserved by the funerary act."